1989
DOI: 10.1136/ard.48.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Factors predicting a poor life prognosis in rheumatoid arthritis: an eight year prospective study.

Abstract: SUMMARY This prospective study evaluates the usefulness of clinical features and measurements of circulating immune complexes and autoantibodies for identification of patients with rheumatoid arthritis with a poor life prognosis. One hundred and seven hospital clinic patients, 64 with extra-articular manifestations, were followed up for a mean period of eight years, during which 50 deaths occurred. Comparison with an age and sex matched control population showed an increased incidence of deaths from myocardial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
50
0
4

Year Published

1993
1993
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(57 citation statements)
references
References 23 publications
3
50
0
4
Order By: Relevance
“…Prediction of mortality by patient questionnaires has now been reported in at least 4 previous independent cohorts of patients with RA: 1) 75 patients studied in 1973, 1982, and 1988, in whom percentages of 74, 20, or 8 activities performed "with ease" on a questionnaire similar to the HAQ identified certain patients whose risk of dying was greater than 50% over the next 5 years (1,42,43); 2) data of Wolfe et a1 indicated prediction of survival according to favorable scores on the HAQ (63); 3) a cohort of 269 patients studied by Kazis et al, in whom higher mortality was seen according to the Arthritis Impact Measurement Scales for mobility and general health perception (66); 41 a cohort of 1,416 patients monitored kom the practices of 15 rheumatologists, in whom MHAQ scores, formal education level, and helplessness scores were independently predictive of 5-year mortality (44). The baseline data in these earlier cohorts did not include standard systematic joint counts or laboratory or radiographic data, which are thought to be prognostic of severe outcomes in RA (5,6,28,31,(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77)(78). In this study, while poorer status in most joint count, radiographic, and laboratory measures were seen in patients who would not survive over the next 5 years, the prognostic value of the questionnaire is as great as or greater than these traditional measures in direct comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…Prediction of mortality by patient questionnaires has now been reported in at least 4 previous independent cohorts of patients with RA: 1) 75 patients studied in 1973, 1982, and 1988, in whom percentages of 74, 20, or 8 activities performed "with ease" on a questionnaire similar to the HAQ identified certain patients whose risk of dying was greater than 50% over the next 5 years (1,42,43); 2) data of Wolfe et a1 indicated prediction of survival according to favorable scores on the HAQ (63); 3) a cohort of 269 patients studied by Kazis et al, in whom higher mortality was seen according to the Arthritis Impact Measurement Scales for mobility and general health perception (66); 41 a cohort of 1,416 patients monitored kom the practices of 15 rheumatologists, in whom MHAQ scores, formal education level, and helplessness scores were independently predictive of 5-year mortality (44). The baseline data in these earlier cohorts did not include standard systematic joint counts or laboratory or radiographic data, which are thought to be prognostic of severe outcomes in RA (5,6,28,31,(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77)(78). In this study, while poorer status in most joint count, radiographic, and laboratory measures were seen in patients who would not survive over the next 5 years, the prognostic value of the questionnaire is as great as or greater than these traditional measures in direct comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical characteristics of the patients are shown in Table 1. The study group comprised 15 females and 5 males, with a median age of 51 years (range 23-72), a median disease duration of 10.5 years (range [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], and a history of failed therapy with standard disease-modifying antirheumatic drugs (DMARDs) (median number of failed DMARDs 4, range 2-7).…”
Section: Methodsmentioning
confidence: 99%
“…Despite optimal use of current antirheumatic therapy, the outcome for many patients with rheumatoid arthritis (RA) consists of pain, disability, and premature death (1)(2)(3). As a response to the need for more effective and less toxic treatment, and to an increase in our understanding of the pathogenic mechanisms in RA, several groups have used monoclonal antibodies as therapeutic agents in this disease (4)(5)(6)(7)(8)(9)(10).…”
mentioning
confidence: 99%
“…The incidence rate of severe extraarticular manifestations in patients with RA has been estimated to be 1 per 100 person-years at risk (4). Patients with severe extraarticular RA have a significantly increased risk of premature mortality compared with those without extraarticular RA (13)(14)(15)(16)(17)(18). It has been suggested that this excess mortality is mainly due to cardiovascular disease (14).…”
mentioning
confidence: 99%